Implementasi Green Accounting dan Profitabilitas pada Perusahaan Consumer Goods Industry yang Tergabung dalam Indeks Saham Syariah Indonesia - Kamilia, Umi; Martini, Tina (IAIN Kudus, 2022)
This study aims to determine the impact of green accounting on the profitability of consumer goods industry companies included in the Indonesian Sharia Stock Index from 2017-2021. Green accounting is represented by environmental performance, costs, and disclosure. The annual reports of ISSI-member corporations in the consumer goods industry sector and the PROPER report from the Ministry of Environment and Forestry for 2017–2021 served as data sources. This research is a quantitative study with panel data regression analysis techniques. Sampling was conducted using a systematic sampling method. During the five-year observation period, the research sample consisted of eight companies that met predetermined requirements. Eviews 12 was used to process data. According to this study’s findings, environmental performance positively affects profitability. Meanwhile, environmental costs and disclosures have no appreciable impact on profitability.